Using motor anticipation exercises and its physical and cognitive components to improve the effectiveness of the defensive skills of volleyball players - Almaghawry Marwan, A. (World Journal of Sport Sciences, 2012)
The research aims to identify the impact of using motor anticipation exercises and its physical and cognitive components on the effectiveness of the effectiveness of the defensive skills of volleyball players. The researcher used the experimental method using the design of the one experimental group and the method of pre and post -test. This study was conducted on a deliberate sample of 12 first-class volleyball players in Benha sport club, registered in the Egyptian Federation of Volleyball for 2011/2012 season, excellent (b). The researcher used tests of physical, cognitive related skills and technical analysis of the skills of defense, as a means of collecting data. The researcher has designed a training program, its duration is10 weeks using the training motor anticipation, exercise, cognitive-related skills in question and the program contains 40 training module by 4 units per week during the period from 23/7/2011 to 29/9/2011. The results showed that the training program had a positive effect on the components of the anticipation motor of physical and cognitive skills under consideration and the results showed that the training program had a positive impact on the effectiveness of the performance of defensive skills (serve reception, block and defense). The training program was the latest homogeneous in terms of all the research variables (physical, cognitive and effective performance of the defensive skills).